‘It’s Video Era’: University Students’ Perception of Asynchronous Learning during Online Speaking Course - Mohammad Fatoni; Iin Widya Lestari (Language Center of Islamic Institute of Uluwiyah (IAI Uluwiyah) Mojokerto Indonesia, 2022)
Studying in university is still using asynchronous during online speaking courses due to technology development and practical consideration. This research aims to analyze the students' perception and the effect of using videos in speaking courses using asynchronous mode. This research used the quantitative research method. The instruments are used questionnaires and tests. The finding shows that the university's students have a positive perception of asynchronous learning mode, and the use of videos, as learning material, have a large effect size on the students’ ability to speak during asynchronous mode. It means the use of video can be recommended to teach speaking in the classroom.